Neonatal Outcome of Pregnancies with Oligohydramnios and Polyhydramnios - Sami, Aqeela; Jalil, Jawad; Sarfraz, Muhammad; Hassan, Jawad ul; Khawar, Ruhma; Mumtaz, Zahra (Pakistan Armed Forces Medical Journal, 2023)
Objective: To asses’ factors associated with neonatal outcome of pregnancies with oligohydramnios and polyhydramnios. Study Design: Comparative Cross-sectional Study. Place and Duration of Study: Department of Pediatrics and Gynecology, Fauji Foundation Hospital, Lahore Pakistan, from Oct 2020 to Sep 2021 Methodology: A prospective comparative study was conducted on the babies born to mothers diagnosed with oligohydramnios and polyhydramnios during the course of pregnancy. Neonates were evaluated by neonatologist within first 24 hours of birth. The cases were admitted and well babies were handed over to parents. The neonatal outcome parameters were observed in all these babies for first two weeks of life. Those who lost follow up they were excluded from study. Age of mother, gestational age of baby, maternal hypertension and maternal diabetes were associated with presence of complications among these babies. Results: Two thousand One hundred and Twenty-nine deliveries took place in given duration. About 322 had either polyhydramnios or oligohydramnios. About 150 cases could be followed completely. Fifty-five (36.7%) showed presence of one or more complications, of which 29(41.4%) cases had oligohydramnios and 26(32.5%) had polyhydramnios. Maternal age and presence of maternal diabetes and maternal hypertension had statistically significant association with complications in neonates (p-value <0.005). Conclusion: Complications rate was high among neonates born to mothers with oligohydramnios or polyhydramnios. Advanced maternal age, presence of diabetes mellitus and hypertension were factors association with presence of complications in neonates included in our study.